EDUCATION OF GRADES 5-6 SELF-CONTROL IN THE PROCESS OF ENGAGEMENT IN MARTIAL ARTS - Hetman, Maryna (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article outlines the peculiarities of self-control training in students of 5-6 grades of education in the process of martial arts classes, the role of martial arts classes, which have a wide arsenal of techniques, forms and work methods for personality education, is updated. It is emphasized that physical and recreational activities and playing sports have a significant impact on the development of not only the physical, but also the moral and intellectual spheres of the individual. The purpose of the article is to determine the peculiarities of self-control in students of the 5th-6th grades of education in the process of practicing martial arts. The main tasks are: to actualize the effects of physical culture and sports on the development of student’ moral and volitional qualities; to determine the structure of education of students’ self-control in 5-6 grades of during martial arts classes; to analyse the ideas of 5-6 grade students about the essential characteristics of the “self-control” phenomenon, to study effective practices of education of students’ self-control in the process of practicing martial arts; to define the value of engaging students in martial arts for the purpose of cultivating self-control. To achieve the goal and solve the research tasks were used such methods as surveys, questionnaires, systematization and data analysis. It was determined that the value of engaging students in martial arts for the purpose of cultivating self-control is the availability of a wide range of methodological tools; the philosophical principles of martial art, where not only physical development is cultivated but also the formation of the personality, the formation of its moral and volitional qualities; creation of conditions for the cultivation of self-control as an important condition for the development of a harmonious, self-sufficient personality; formation of ideas of 5-6 grade students about values and moral attitudes inherent in a harmoniously developed personality; pedagogical support, due to which every students has opportunities for progress based on an individual approach. Teachers and trainers consider the training process as the main type of activity to be the most important for the education of moral and volitional qualities, in particular, self-control. Modelling of situations, creative tasks, conversations and discussions are important complementary influences in educating students’ self-control in 5-6 grades in the process of practicing martial arts.